A Tiny RNA that Packs a Big Punch: The Critical Role of a Viral miR-155 Ortholog in Lymphomagenesis in Marek’s Disease - Zhuang, Guoqing; Sun, Aijun; Teng, Man; Luo, Jun (Frontiers in Microbiology, 2017)
MicroRNAs (miRNAs) are small non-coding RNAs that have been identified in animals, plants, and viruses. These small RNAs play important roles in post transcriptional regulation of various cellular processes, including development, differentiation, and all aspects of cancer biology. Rapid-onset T-cell lymphoma of chickens, namely Marek’s disease (MD), induced by Gallid alphaherpesvirus 2 (GaHV2), could provide an ideal natural animal model for herpesvirus-related cancer research. GaHV2 encodes 26 mature miRNAs derived from 14 precursors assembled in three distinct gene clusters in the viral genome. One of the most highly expressed GaHV2 miRNAs, miR-M4-5p, shows high sequence similarity to the cellular miR-155 and the miR-K12-11 encoded by Kaposi’s sarcoma-associated herpesvirus (KSHV), particularly in the miRNA “seed region”. As with miR-K12-11, miR-M4-5p shares a common set of host and viral target genes with miR-155, suggesting that they may target the same regulatory cellular networks; however differences in regulatory function between miR-155 and miR-M4-5p may distinguish non-viral and viral mediated tumorigenesis. In this review, we focus on the functions of miR-M4-5p as the viral ortholog of miR-155 to explore how the virus mimics a host pathway to benefit the viral life cycle and trigger virus-induced tumorigenesis.